PENGARUH IKLIM KERJA TERHADAP PRODUKTIVITAS KERJA DOSEN PERGURUAN TINGGI SWASTA ACEH - Yusaini Yusaini; Indra Utama (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
This study aims to determine the magnitude of the value of the influence of the work climate on the work productivity of private university lecturers in Aceh Province. The population of this research is the number of lecturers in 8 (eight) private universities in Aceh Province, namely Gajah Putih Takengon University, Al Muslim Bireuen University, Gunung Leuser University Aceh, Jabal Ghafur Sigli University, Abulyatama University, Muhammadiyah University Aceh, Serambi Mekah University Banda Aceh, Usman Safri High School, with a total of 1769 people, while the number of samples taken by proportional sampling is 313 people. The research instrument used a questionnaire with a Likert scale. The research data were analyzed with a simple regression analysis that began with the analysis requirements test, including normality test, linearity test and significance of a regression. The results showed that; the work climate directly determines the work productivity of Aceh's private lecturers by 0.3512 = 0.09, the rest is influenced by other variables outside of this research variable. Conclusion of the regression test of 9% and the results of the linearity calculation obtained a simple regression equation Y = 44.79 + 0.41X. This shows that work productivity is influenced by the competence of lecturers.